2019
DOI: 10.1108/ajems-01-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Service recovery satisfaction and customer commitment in the airline business

Abstract: Purpose The purpose of this paper is to examine the precursors and outcomes of service recovery satisfaction and customer commitment among airline business customers. Design/methodology/approach Data were collected from airline travellers in South Africa using a structured questionnaire. Structural equation modelling was used to analyse the proposed hypotheses. Findings The results revealed that recovery expectations and perceived equity exert significant influence on levels of recovery satisfaction, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 49 publications
1
19
1
1
Order By: Relevance
“…The example does not typically address the severity of service failures, like those that result in injury or death to the Airline Industry. Matikiti et al (2018) also found that service failure has a positive effect on service recovery. Research from Christina et al (2019) also found a positive influence on the relationship between fairness in service recovery and customer loyalty.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The example does not typically address the severity of service failures, like those that result in injury or death to the Airline Industry. Matikiti et al (2018) also found that service failure has a positive effect on service recovery. Research from Christina et al (2019) also found a positive influence on the relationship between fairness in service recovery and customer loyalty.…”
Section: Introductionmentioning
confidence: 88%
“…If it is not handled correctly, it can result in negative things for the company, which will lead to customer dissatisfaction (Hua, 2012). Therefore, service companies must avoid losing customers to remain profitable and learn to be better at responding to service failure properly (Matikiti et al, 2018). The service recovery efforts are the most effective way to ensure customers meet the desired expectations (Pai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted in an offline context like restaurants, retailing, and the airline sector (Borah et al, 2020;Cheng et al, 2019;Matikiti et al, 2019). Furthermore, prior research mainly focused on experimental studies that provide service failure scenarios and asked the customers to put them in that scenario and respond to the subsequent question (Koc et al, 2019;Wei et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…; (Hill Cummings & Yule, 2020); (Mostafa et al, 2015); (Yani-de-Soriano et al, 2019); (Ruiz-Molina et al, 2020); (Babin et al, 2021); (Jahandideh et al, 2014); (Donoghue & De Klerk, 2010); (Schaefers & Schamari, 2016 (Čater & Čater, 2010); (Lariviere et al, 2014); (Homburg et al, 2014); (Keiningham et al, 2015) ; (Shukla et al, 2016); (Izogo, 2017); (Matikiti et al, 2019); (Fatima & Mascio, 2020 (Rosario et al, 2016); (Yang et al, 2018); (Ruvio et al, 2020); (Sweeney et al, 2020); (Verma & Yadav, 2021 Wang et al, 2013) ; (Pradhan, 2014); (Choi & Choi, 2014)…”
mentioning
confidence: 99%
“…Casielles et al, 2017);(Young & Seock, 2017);(Maxham, 2020) ‫تلت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اوص‬ ‫التخ‬ ‫ن‬ ‫ي‬ ‫تا‬ ‫ايج‬ ‫معنو‬ ‫تاب‬ ‫اراث‬ ‫لجود‬ ‫إ‬ ‫تة‬ ‫تدم‬ ‫ادم‬ ‫تةا‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫إص‬ ‫تة‬ ‫تاحي‬ ‫ن‬ ‫من‬ ‫تاده‬ ‫لأبع‬ ‫تة‬ ‫اإللكارلني‬ ‫تة‬ ‫اةنطو‬ ‫تة‬ ‫لالكلء‬ ‫من‬ ‫تا‬ ‫تادا‬ ‫لأبع‬ ‫من‬ ‫تل‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫تة‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اس‬ ‫در‬ ‫مع‬ ‫تت‬ ‫ت‬ ‫ت‬ ، ‫اا‬ ‫تا‬ ‫ت‬ ‫ت‬ ‫ملء‬ ‫أخرى.‬ ‫تة‬ ‫ت‬ ‫ت‬ ‫تاحي‬ ‫ت‬ ‫ت‬ ‫ن‬(Mattila, 2015);(Tektas, 2017);(Matikiti et al, 2019) ‫التخ‬ ‫لجود‬ ‫إ‬ ‫تلت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اوص‬ ‫معنو‬ ‫اراثاب‬ ‫ي‬ ‫إيجا‬ ‫ادمدمة‬ ‫تةا‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫إص‬ ‫ن‬ ‫ت‬ ‫العة‬ ‫ه‬ ‫ت‬ ‫ت‬ ‫ا‬ ‫تة‬ ‫ت‬ ‫ةعر‬ ‫تة‬ ‫ت‬ ‫الهيكلي‬ ‫تا‬ ‫ت‬ ‫الثن‬ ‫تة‬ ‫ت‬ ‫تادل‬ ‫ت‬ ‫مع‬ ‫تدام‬ ‫ت‬ ‫تتخ‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫تاس‬ ‫ت‬ ‫ن‬ ‫تاا‬ ‫ت‬ ‫العة‬ ‫ه‬ ‫ت‬ ‫ت‬ ‫له‬ ‫اة،ارا‬ ‫النءوذال‬ ‫تداد‬ ‫ت‬ ‫تاال‬ ‫ت‬ ‫ن‬ ‫تا‬ ‫ت‬ ‫تاحث‬ ‫ت‬ ‫الث‬ ‫تام‬ ‫ت‬ ‫الل‬ ‫ينص‬ ‫ت‬ ‫ت‬ ‫لال‬ ‫تم‬ ‫ت‬ ‫الث‬ ‫رلض‬ ‫من‬ ‫تايي‬ ‫ت‬ ‫الث‬ ‫رض‬ ‫لل‬ ‫تة‬ ‫ت‬ ‫تث‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ي‬ ‫تال‬ ‫ت‬ ‫ا‬ ‫إل‬ ‫معنو‬ ‫أير‬ ‫تد‬ ‫ت‬ ‫يوج‬ ‫ص‬ ‫تة‬ ‫ت‬ ‫الكلء‬ ‫الل‬ ‫تة‬ ‫ت‬ ‫تدم‬ ‫ت‬ ‫ادم‬ ‫تةا‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ص‬ ‫ا،ييم‬ ‫ام‬ ‫،د‬ ‫اإللكارلنيةج‬ ‫ة‬ ‫اةنطو‬ : ‫يل‬ ‫ملءا‬ ‫رالية‬ ‫رلض‬ ‫مجءوالة‬ ‫إ‬ ‫الثايي‬ ‫رض‬ ‫ال‬ ‫ملءتغي‬ ‫ر‬ ‫ت‬ ‫ت‬ ‫ي‬ ‫لالت‬ ‫ارج‬ ‫اصالت‬ ‫من‬ ‫لكل‬ ‫ي‬ ‫إيجا‬ ‫معنو‬ ‫ر‬ ‫اوي‬ ‫يوجد‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫الل‬ ‫تت،لة‬ ‫ت‬ ‫مي‬ ‫اا‬ ‫ر‬ ‫معنوية‬ ‫تتوى‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫مي‬ ‫تد‬ ‫الن‬ ‫اابع‬ ‫ر‬ ‫ملءتغ‬ ‫تدر‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اةال‬ ‫تة‬ ‫جاذني‬ 0.05 . ‫تانة‬ ‫تتج‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اصس‬ ‫من‬ ‫تل‬ ‫لك‬ ‫ي‬ ‫تا‬ ‫إيج‬ ‫معنو‬ ‫ر‬ ‫اوي‬ ‫يوجد‬ ‫تا‬ ‫ملء‬ ‫معنوية‬ ‫تتوى‬ ‫ت‬ ‫مي‬ ‫الند‬ ‫اابع‬ ‫ر‬ ‫ملءتغ‬ ‫تدر‬ ‫ت‬ ‫اةال‬ ‫جاذنية‬ ‫الل‬ ‫تت،لة‬ ‫ت‬ ‫مي‬ ‫اا‬ ‫ر‬ ‫ملءتغ‬ ‫لالتعويض‬ ‫تكةاج‬ ‫ت‬ ‫اةش‬ ‫لحل‬ ‫وريةج‬ ‫ال‬ ‫اا‬ ‫ر‬ ‫للءتغ‬ ‫ية‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ي‬ ‫ال‬ ‫األاءية‬ ‫الن‬ ‫تف‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫اكش‬ ‫اةعامةا‬ ‫ه‬ ‫لا‬ ‫معاد‬ ‫داخل‬ ‫تت،لة‬ ‫ت‬ ‫ت‬ ‫اةي‬ ‫أ‬ ‫منفا‬ ‫لاث‬ ‫التابعج‬ ‫ر‬ ‫ناةتغ‬ ‫ثي‬ ‫الت‬ ‫دار‬ ‫اصن‬ ‫لة‬ ‫تدر‬ ‫ت‬ ‫ت‬ ‫اةال‬ ‫جاذنية‬ ‫الل‬ ‫ا‬ ‫ر‬ ‫اوي‬ ‫األملمر‬ ‫ر‬ ‫اةتغ‬ ‫التعويض‬ ‫او‬ ‫يلي‬ ‫ار.‬ ‫اصالت‬ ‫ا‬ ‫ر‬ ‫لأخ‬ ‫ر‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ي‬ ‫الت‬ ‫يم‬ ‫ورية‬ ‫ال‬ ‫تتجانة‬ ‫ت‬ ‫ت‬ ‫اصس‬ ‫يم‬ ‫تكةا‬ ‫ت‬ ‫ت‬ ‫اةش‬ ‫حل‬ ‫وريةج‬ ‫ال‬ ‫تانة‬ ‫تتج‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫لاصس‬ ‫رج‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ي‬ ‫لالت‬ ‫ارج‬ ‫ت‬ ‫اصالت‬ ‫من‬ ‫تل‬ ‫لك‬ ‫ي‬ ‫تا‬ ‫إيج‬ ‫معنو‬ ‫ر‬ ‫اوي‬ ‫يوجد‬ ‫ملءتغي‬ ‫اةالدر‬ ‫ية‬ ‫مالدا‬ ‫الل‬ ‫ميت،لة‬ ‫اا‬ ‫ر‬ ‫ملءتغ‬ ‫لالتعويض‬ ‫اةشكةاج‬ ‫لحل‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫األملث‬ ‫ر‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ت‬ ‫ورية‬ ‫ال‬ ‫تتجانة‬ ‫اصس‬ ‫او‬ ‫تدر‬ ‫اةال‬ ‫ية‬ ‫تدا‬ ‫مال‬ ‫الل‬ ‫ا‬ ‫ر‬ ‫اوي‬ ‫ر‬ ‫يلي‬ ‫التعويضج‬ ‫يم‬ ‫يم‬ ‫رج‬ ‫ت‬ ‫ي‬ ‫الت‬ ‫ار‬ ‫اصالت‬ ‫ا‬ ‫ر‬ ‫لأخ‬ ‫اةشكةا‬ ‫حل‬ ‫الثايي.‬ ‫رع‬ ‫ال‬ ‫رض‬ ‫ال‬ ‫خطو‬ ‫يثوا‬ ‫يته‬ ‫جج‬ ‫النتا‬ ‫ه‬ ‫ا‬ ‫لمن‬ .…”
unclassified